PENGARUH KARAKTERISTIK INDIVIDU, KEPEMIMPINAN, DAN KOMPETENSI TERHADAP KINERJA PEGAWAI DI UPTD BAPELKESEMAS DINAS KESEHATAN PROVINSI BALI - Ni Komang Wahyuni; I Nengah Suardhika; Putu Agus Eka Rismawan (EMAS, 2023)
This research was conducted based on research on gaps and differences focusing on individual characteristics, leadership and competency on employee performance. In addition, there are also research problems regarding reducing work targets at the UPTD BAPELKESEMAS Bali Provincial Health Office. This research was conducted at UPTD BAPELKESEMAS Bali Provincial Health Office with a sample of 51 respondents taken using a saturated census. All data obtained from distributing questionnaires, then analyzed using multiple linear regression, hypothesis testing (t test and f test). The results of the study show that (1) individual characteristics, leadership and competence simtultaneously have a positive and significant effect on employee performance at the UPTD BAPELKESEMAS Health Office of the Province of Bali. (2) individual characteristics have a positive and significant effect on employee performance. (3) leadership has a positive and significant effect on employee performance. (4) competence has a positive and significant effect on employee performance.